Fabrication of Nanowire Channels with Unidirectional Alignment and Controlled Length by a Simple, Gas-Blowing-Assisted, Selective-Transfer-Printing Technique - Kim, Yong-Kwan; Kang, Pil Soo; Kim, Dae-Il; Shin, Gunchul; Kim, Gyu Tae; Ha, Jeong Sook (Small (Weinheim an der Bergstrasse, Germany), 2009)
A printing‐based lithographic technique for the patterning of V2O5 nanowire channels with unidirectional orientation and controlled length is introduced. The simple, directional blowing of a patterned polymer stamp with N2 gas, inked with randomly distributed V2O5 nanowires, induces alignment of the nanowires perpendicular to the long axis of the line patterns. Subsequent stamping on the amine‐terminated surface results in the selective transfer of the aligned nanowires with a controlled length corresponding to the width of the relief region of the polymer stamp. By employing such a gas‐blowing‐assisted, selective‐transfer‐printing technique, two kinds of device structures consisting of nanowire channels and two metal electrodes with top contact, whereby the nanowires were aligned either parallel (parallel device) or perpendicular (serial device) to the current flow in the conduction channel, are fabricated. The electrical properties demonstrate a noticeable difference between the two devices, with a large hysteresis in the parallel device but none in the serial device. Systematic analysis of the hysteresis and the electrical stability account for the observed hysteresis in terms of the proton diffusion in the water layer of the V2O5 nanowires, induced by the application of an external bias voltage higher than a certain threshold voltage. Directional blowing of N2 gas onto patterned polymer stamps inked with randomly distributed V2O5 nanowires induces alignment of the nanowires perpendicular to the long axis of the line patterns (see picture). Subsequent transfer of the nanowires on the relief region of the patterned stamp results in the selective transfer of aligned nanowires with a controlled length.